Perbuatan Meiawan Hukum Oleh Penguasa Serta Perkembangan Perma Nomor 2 Tahun 2019 Studi Kasus Perkara Nomor 168/Pdt-G/2018/Pn.Tjk - Alfian Dimas Saputra; Mikhail Alif; Mokhamad Naufal Islami (Peneliti.net, 2023)
Law, there are errors caused by offenders, there are factor that result for victims, and there is a relationship between one that is committed to carrying a loss. The element of this element applies cumulatively, in the sense that if there is one of the elements above cannot be fulfilled, then an act that is carried out cannot be charged article against the law. Acts of Against Law by the Ruler are listed and regulated in Supreme Court Regulation Number 2 of 2019. One form of his case occurred by the ruler which occurred in the city of Lampung. This action is more exact in the Griya Market in Lampung. His chronology in the agenda for a Pasar Tanah Court to the Tjg Court. Coral. The land is open with the widest of 3000m 2 which will be given for the purposes of building the Prosecutor’s Office in a new manner. This problem occurred because the eviction was carried out by giving relocation to residents and violating the careful principle in acting because the actions carried out detrimental to the community